Effect of postoperative residual astigmatism on visual outcomes after trifocal intraocular lens implantation - Zhang, Limei; Shen, Wenqian; Shen, Jiying; Wang, Min; Ni, Shuang; Guo, Haike; Yang, Jin (Frontiers in Medicine, 2023)
Purpose The aim of this study was to evaluate the effect of residual astigmatism on postoperative visual outcomes after trifocal intraocular lens implantation. Methods In this prospective observational study, we divided 156 eyes into two groups according to postoperative astigmatism measured by subjective optometry and followed them up for 3 months. Visual acuity, modulation transfer function (MTF) curves, Strehl ratio (SR), Visual Function Index-14 scores, and photic phenomena were compared. Results Linear regression analysis revealed a weak correlation between residual astigmatism and uncorrected distance visual acuity (UDVA) (r = 0.190, P = 0.016) at 3 months and a significant between-group difference at 1- and 3-month postoperative UDVA (P = 0.038, P = 0.018, respectively). MTF curve values and SR (MTF-10 total, MTF-10 cornea, MTF-30 total, MTF-30 cornea, SR Total, and SR cornea) were significantly worse (P < 0.001), and the Visual Function Index-14 scores were lower in the 0.5 < astigmatism ≤ 1.25 D group (P < 0.05) than in the astigmatism ≤ 0.5 D group. No significant differences were found in the frequency, severity, and bothersomeness of photic phenomena (P > 0.05). Conclusion Postoperative residual astigmatism affects the UDVA of the trifocal intraocular lens-implanted eyes. Although we found no significant differences in uncorrected intermediate and near visual acuity, both objective and subjective visual quality were affected, suggesting the need for surgical planning when the anticipated postoperative astigmatism is >0.5 D.